STRATEGI MANAJEMEN KEUANGAN SEKOLAH DASAR NEGERI NON RSDBI DAN SDBI - Bambang Soepeno (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
Abstract: Educational fund is one of variables influences to quality of schools’ performance. After Bupati Act no. 188.45/255/012/2009 published, Schools’ committee could draw education fund from parents. There were some conclusions from this research: (1) education fund was a determinant factor guaranted effective schools’ performance; (2) Fund management authority of schools’ commit-tee could enhance bargaining power when they met Schools’ principal; (3) Schools’ educational fund transparancy and accountability had a signficant contribution to improvement of parents’ care toward schools’ management and improvement of school images. Key words: Schools’ fund management, school comitee, educational fund download PDF fulltext